Gentamicin pre- soaking of hamstring autografts decreases infection rates in anterior cruciate ligament reconstruction. (2021) - Moriarty, P.; Kayani, B.; Wallace, C.; Chang, J.; Plastow, R.; Haddad, F. S.
No abstract available